In Cell NMR Spectroscopy: Investigation of G-Quadruplex Structures Inside Living Xenopus laevis Oocytes - Krafcikova, Michaela; Hänsel-Hertsch, Robert; Trantirek, Lukas; Foldynova-Trantirkova, Silvie (Methods in molecular biology (Clifton, N.J.), 2019)
G-quadruplexes are inherently polymorphic nucleic acid structures. Their folding topology depends on the nucleic acid primary sequence and on physical-chemical environmental factors. Hence, it remains unclear if a G-quadruplex topology determined in the test tube (in vitro) will also form in vivo. Characterization of G-quadruplexes in their native environment has been proposed as an efficient strategy to tackle this issue. So far, characterization of G-quadruplex structures in living cells has relied exclusively on the use of Xenopus laevis oocytes as a eukaryotic cell model system. Here, we describe the protocol for the preparation of X. laevis oocytes for studies of G-quadruplexes as well as other nucleic acids motifs under native conditions using in-cell NMR spectroscopy.
Keywords: Nucleic Acids; Animals; G-kvadruplexy; magnetická rezonanční spektroskopie; DNA; Xenopus laevis; zvířata; G-Quadruplexes; Magnetic Resonance Spectroscopy; Xenopus laevis oocyte; nukleové kyseliny; In-cell NMR; RNA; G-quadruplex